Efektivitas Penerapan Guided Discovery Learning untuk meningkatkan Hasil Belajar Siswa Mata Pelajaran Dasar-Dasar Ketenagalistrikan - Muhammad Fajhri; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the effectiveness of the guided discovery learning model on improving student learning outcomes in the Basics of electrical electricity subjects at SMK Negeri 1 Lintau Buo. This study uses a type of experimental research that is categorized into quasi-experimental research types with pretest-posttest control group design designs. The subjects of this study were grade X TK students of SMK Negeri 1 Lintau Buo in the 2023/2024 school year consisting of 30 students In this study, the data collection method used was pretest and posttest questions which were validated by expert weighers, namely subject expert lecturers and subject teachers. Before the treatment is given, pretest questions are given and after the treatment is given at the end of learning, posttest questions will be given. The results of the pretest (initial test) show the value before learning is given treatment and the results of the posttest (final test) show the value after learning is given treatment. These results can be seen based on the realm of knowledge, namely pretest and posttest results analyzed using a series of tests such as prerequisite tests, N-Gain Score and Effect size which fall into the very large category and use the percentage of completeness of learning outcomes increased from the very low to very high category. Thus, the guided discovery learning learning model improves student learning outcomes in the Basics of electricity subjects.